95 PENGARUH FAKTOR-FAKTOR KEUANGAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN - Haryanto, M. Y. Dedi (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2015)
This research aims to know the influence of the liqudity, growth, profitability and efficiency to dividend policy. The population of this research are companies listed on the Indonesia stock exchange and the sample frame use the list of the 50 leading companies in market capitalization in 2012. The sampling methode is purposive sampling technique with two criteria and final sample are 36 listed company. Data was collected from the Indonesian Capital Market in 2012 with research period 2008-2010. This research use multiple regression to analysis data. There are one dependent variables and four independent variables. The results showed that at the level of 95%, ROE, DER, and OPM influence dividend policy while net income growth does not affect the dividend policy. But with 90% confidence, results showed that net income growth (GROW) affect dividend policy. So it can be concluded that corporate financial factors influence the dividend policy.